Cultural Representation in EFL Textbooks for Young Learners: A Comparative Analysis of Local, Target, and International Cultures - Kafah, Aulia Zilmi; Pujiani, Tri; Soali, Muhammad; Sukmawati, Ida Dian (Universitas Harapan Bangsa, 2025)
Incorporation of cultural materials into EFL textbooks play a crucial role in the development of the linguistic abilities and the cultural consciousness of young learners. The balance between local, target, and international cultures forms the key theme of this study of cultural information presentation in EFL textbooks for young learners. This study investigates cultural representation in Indonesian young learners' EFL textbooks with a focus on the balance between the local, target, and international cultures. Based on content analysis of the My Next Words series, the study concludes a dominant representation of local culture, raising issues about limited intercultural exposure. The study concludes that more culturally balanced material is needed to foster global awareness and intercultural competence among learners.